(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
The aim of present investigation was to develop an optimized buccoadhesive film of metoprolol tartrate, a BCS class I drug, to provide unidirectional sustained drug delivery to the buccal mucosa that has potential to enhance the bioavailability. The films were prepared using HPMC K4M as film former, carbopol 934 P as buccoadhesive polymer and dimethyl sulfoxide as penetration enhancer, by solvent casting technique. The films were characterized for various pharmacotechnical parameters and 23 full factorial design was employed to study the effect of independent variables. The design was validated by extra design checkpoint formulation (BF9). The response of design was employed to study the effect of independent variables. The responses of design were analyzed using Design Expert 8.0.7.1 and the analytical tools of software were used to draw pareto charts. On the basis of software analysis, formulation BF4 with desirability factor of 0.698 was selected as optimized formulation and was evaluated for independent parameters. Optimized formulation showed 12.05 hr, ex-vivo residence time, and good permeation (42.68%) through goat buccal mucosa and 82.19% drug release after 8th hour. The release kinetics of optimized formulation best fitted the higuchi model. Histopathological studies revealed no buccal mucosal damage. Hence BF4 formulation can be concluded as promising drug delivery system to enhance the permeability limited absorption of metoprolol tartrate. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22130 Bangladesh J. Sci. Ind. Res. 49(3), 165-172, 2014